ALGORITHMS AND SOFTWARE OF WHITENING OF NOISE IN THE RECEPTION OF BROADBAND CHIRP SIGNALS IN THE HF COMMUNICATION CHANNEL - Ivanov, Vladimir; Ivanov, Dmitriy; Ryabova, Natalya; Ryabova, Maria; Chernov, Andrei; Elsukov, Alexey (Journal of Applied Engineering Science, 2015)
Scientific substantiation of the adaptive algorithm whitening noise in the HF band when receiving a continuous chirp signal is given. The software implementation of the algorithm is presented. Full-scale experiments using the developed device with a continuous chirp signal based on the technology of software-defined radio systems were conducted. It is established that whitening tends to equalize noise level throughout the HF band. Some rare emissions of whitening spectrum do not exceed the range of 10 dB.